Heartworm disease in Ukraine: a rapid transition from a sporadic disease to a widespread pathology. Clinical case - Bovsunovska, Kateryna; Chepilko , Katerina (The Ukrainian Scientific Medical Youth Journal, 2025)
meteorological observations of recent decades have shown significant climatic changes, called global warming, throughout the world and in Ukraine, in particular.[5]. This, in turn, could not but affect the prevalence of various infectious diseases, including helminthiasis, not typical of a temperate climate in our country. We are talking, in particular, about dirofilariasis - a transmissible parasitic biohelminthiasis, which is caused by the larval stage of helminths of the genus Dirofilaria and can cause cardiac, hepatic, renal symptoms and damage to the subcutaneous tissue. Their development occurs with a double change of hosts: final and intermediate. The final hosts of dirofilaria are carnivorous animals of the canine and feline families, in which adult parasites are located in the subcutaneous connective tissue. They are the source of invasion. Intermediate hosts and vectors are mosquitoes of the genera Anopheles, Culex, Aedes. The vectors can be ticks, fleas, other insects. Humans are facultative, accidental and final hosts of helminths. Dirofilaria are thin filamentous round worms of white color, belonging to the class Nematoda, order Spirurida, family Filariidae, genus Dirofilaria. The genus Dirofilaria includes almost 20 species, but only three have been registered in Ukraine: D. repens, D. immitis, and D. ursi. In Ukraine, only D. repens, which causes subcutaneous dirofilariosis in humans, has been known to infect humans. This helminthiasis is a disease typical of countries with a tropical climate. However, cases of dirofilariosis are now increasingly being registered in temperate continental climates, as a result of which Ukraine has left the list of low-risk areas to which it previously belonged. [3]. In addition to climate change, a significant role in increasing the prevalence of heartworm disease in Ukraine is played by active migration processes, weak veterinary control over the import of infested pedigree animals into non-endemic territories, uncontrolled number of stray animals, ignorance of this disease by specialists of medical and veterinary services, lack of established diagnostic methods, which makes this pathology extremely relevant and requires taking appropriate measures. [4]. In the article, we present a description of a clinical case of heartworm disease in a patient who did not travel outside Ukraine. Due to the lack of awareness of this pathology among many Ukrainian doctors, their lack of experience in working with heartworm disease, and the lack of established diagnostic methods, this disease is rarely diagnosed immediately at the first visits of patients, they are often given incorrect diagnoses and, accordingly, are prescribed treatment that does not improve the condition of patients. Considering all the above factors, it is worth concluding that appropriate measures should be taken to improve the diagnosis, treatment and prevention of heartworm disease and other "new" infectious diseases for Ukraine.